Kuta, Bali: From Port City to Surf City - Wijaya, I Nyoman; Lestari, Sri (Diponegoro University, 2024)
Kuta’s port, once the center of Bali’s maritime trade, was gradually replaced by Buleleng’s port around the 1860s. The once-bustling Kuta dwindled into a small, impoverished village. However, by 1937, Kuta began attracting surf tourists, spurred by the opening of the Kuta Beach Hotel, which also offered surfing lessons to its guests. In 1942, the hotel was burned down by Japanese occupying forces, halting surfing activities until the late 1960s, when American hippie tourists revived the scene. They were followed by Australian hippies in 1973, leading to the spread of surfing across Bali’s white-sand, high-wave beaches. Unintentionally, this became the foundation of Kuta’s beach tourism. The evolution of Kuta from a harbor to a surfing port represents a compelling maritime historical phenomenon that merits further scholarly investigation. Data was gathered from surfers’ memoirs on websites and the collective memory of Denpasar youth active in Kuta during the 1960s–1970s, supplemented by humanities research on Kuta. This study reveals Kuta’s transformation into a Surf City, along with its accompanying socio-economic and cultural effects.